2006
DOI: 10.4315/0362-028x-69.8.2007
|View full text |Cite
|
Sign up to set email alerts
|

Carriage of Bacteria by Proboscises, Legs, and Feces of Two Species of Flies in Street Food Vending Sites in Ouagadougou, Burkina Faso

Abstract: Flies are widely recognized as potential reservoirs and vectors of bacteria. In the present study, an attempt was made to assess meat-poultry and local fruit juice processing and vending sites for their hygienic status and the presence of houseflies, Musca domestica, and blow flies, Lucilia caesar, for bacterial carriage. The hygienic status results revealed the presence of waste and sewage nearby which provided food and harborage for flies. On the two sites, the M. domestica population was dominant ranging fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 23 publications
1
35
0
2
Order By: Relevance
“…There is no liquid discharge system, which leads to an accumulation of dirty water and garbage that may attract flies and other insects. Studies (Barro et al, 2006;Muinde & Kuria, 2005) indicate that an unsafe place for the preparation and sale of street food, marked by the presence of various solid waste liquid provides a favorable environment for flies and other insects. Other studies (de Jesus et al, 2004;Szalanski et al, 2004) showed that insects play an important role in the transmission of pathogenic microorganisms that cause infections.…”
Section: Hygiene Practices In the Manufacturing Process Of Skewered Meatmentioning
confidence: 99%
See 2 more Smart Citations
“…There is no liquid discharge system, which leads to an accumulation of dirty water and garbage that may attract flies and other insects. Studies (Barro et al, 2006;Muinde & Kuria, 2005) indicate that an unsafe place for the preparation and sale of street food, marked by the presence of various solid waste liquid provides a favorable environment for flies and other insects. Other studies (de Jesus et al, 2004;Szalanski et al, 2004) showed that insects play an important role in the transmission of pathogenic microorganisms that cause infections.…”
Section: Hygiene Practices In the Manufacturing Process Of Skewered Meatmentioning
confidence: 99%
“…They provide the mechanical transmission of germs from one place to another landing on contaminated surfaces (waste or feces) and on the food briefly opened. Large populations of two species of flies have been identified on the websites selling street food: it is the housefly and green fly respectively Musca domestica and Lucilia caesar (Barro et al, 2006). The observations revealed that these two insects flit and are often found in foods.…”
Section: Hygiene Practices In the Manufacturing Process Of Skewered Meatmentioning
confidence: 99%
See 1 more Smart Citation
“…The vector potential of M. domestica has been proved for the propagation of protozoan (amoebic dysentery), bacterial (shigellosis, salmonellosis, cholera), helminthic (round worms, hookworms, pinworms and tapeworms), viral (Turkey Corona virus, Reticuloendotheliosis virus, H5N1 influenza virus) and rickettsial infections, among others [4]. The study by Barro et al [6], revealed M. domestica to be predominant fly associated with street-food vendors in Ouagadougou which carried isolates of Coliform, Salmonella, Shigella, Staphylococci and Streptococci on both their legs and proboscis, while Barin et al [7], demonstrated presence of Newcastle disease virus in the significant number of adult muscid flies collected from 20 poultry farms near Tehran, Iran. Furthermore, recent reports about carriage of antibiotic-resistant pathogens by M. domestica collected from different fast-food restaurants in northern Kansas (USA) [8] and in hospitals of several countries of Sub-Saharan Africa [9] are quite alarming and calls for urgent M. domestica control measures.…”
Section: Introductionmentioning
confidence: 99%
“…dan Staphylococcus spp. (Almeida et al 2014), melalui alat probosis, serta organ tubuh bagian luar terutama tungkai (Barro et al 2006) ketika melakukan aktifitas makan dan bereproduksi (Nayduch et al 2013). Selanjutnya, agen penyakit yang telah masuk atau melekat pada organ tubuh tersebut dipindahkan ke materi makanan ternak dan pada gilirannya mikroorganisme patogen terinfeksi pada ternak yang mengkonsumsi makanan tersebut (Zurek & Ghosh 2014).…”
unclassified